2011
DOI: 10.1111/j.2042-3292.2011.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Otitis media‐interna and secondary meningitis associated withCorynebacterium pseudotuberculosisinfection in a horse

Abstract: Summary A one‐year‐old Thoroughbred colt was evaluated because of facial nerve paralysis, ataxia and fever. Neurological evaluation found the colt to be obtunded and grade 3/5 ataxic in all 4 limbs. Right‐sided facial nerve paralysis was present and a large, deep corneal ulcer noted in the right eye. Signs of vestibular disease were also present, including circling towards the right and horizontal nystagmus. A complete blood count showed mild leucocytosis, neutrophilia and hyperfibrinogenaemia. A computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…Most clinicians do not perform transtypanocentesis. However, in the current report by Rand et al . (2012), the horse was showing evidence of central nervous disease that required further diagnostics (CT and CSF collection) that warranted general anaesthesia.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…Most clinicians do not perform transtypanocentesis. However, in the current report by Rand et al . (2012), the horse was showing evidence of central nervous disease that required further diagnostics (CT and CSF collection) that warranted general anaesthesia.…”
contrasting
confidence: 70%
“…In the report by Rand et al (2012), otitis media-interna resulting in meningitis was reported to be uncommon in the horse. Diseases affecting the ear are described according to their anatomical location.…”
mentioning
confidence: 96%
“…; Rand et al . ). To understand the prevalence of this infection better, bacteriological, serological and molecular diagnoses must be promoted to identify the causal agent and develop an improved therapeutic solution.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of infection by this agent in horses is higher than expected, probably because it is an underdiagnosed condition in all of its previously reported clinical manifestations, many of which are uncommon, such as pericarditis, pleuritis, facial cellulitis, paniculitis, otitis mediainterna and meningitis (Farstvedt et al 2004;Perkins et al 2004;Rand et al 2012). To understand the prevalence of this infection better, bacteriological, serological and molecular diagnoses must be promoted to identify the causal agent and develop an improved therapeutic solution.…”
Section: Discussionmentioning
confidence: 99%
“…; Koch and Witte ), otitis media or interna (Rand et al . ), fractures of the temporal bone (Pownder et al . ), encephalitis (Barton et al .…”
Section: Discussionmentioning
confidence: 99%